Area-Efficient Digital Design Using RRAM-CMOS Standard Cells - Fritscher, Markus; Uhlmann, Max; Ostrovskyy, Philip; Reiser, Daniel; Chen, Junchao; Schubert, Andreas; Schulze, Carsten; Kahmen, Gerhard; Fey, Dietmar; Reichenbach, Marc; Krstic, Milos; Wenger, Christian (2024 IEEE Computer Society Annual Symposium on VLSI (ISVLSI), 2024)
Extending the scalability of digital integrated circuits through novel device concepts is an attractive option. Among these concepts, resistive random access memory (RRAM) devices allow fast and nonvolatile operation. However, building large memristive systems is still challenging since large analog circuits have to be designed and integrated. In this paper, we propose a novel solution - the implementation of digital standard cells by the means of RRAM devices. While this methodology is universal, with applications ranging from few-device-circuits to large macroblocks, we demonstrate it for a 2T2R-cell. The benefits of using RRAM devices are demonstrated by implementing a NAND standard cell merely consuming the area of two transistors. This cell is about 25 % smaller than the equivalent CMOS NAND in the same technology. We use these cells to implement a half adder, beating the area of the equivalent CMOS implementation using more sophisticates gates by 15 %. Lastly, we fully integrate this novel standard cell into a digital standard cell library and perform a synthesis and layout of a RISC-V CPU core.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Application specific integrated circuit; Circuit synthesis; Logic Gates; Resistive RAM; RISC-V; VLSI